2008
DOI: 10.1002/cncr.23814
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulation for the initial treatment of venous thromboembolism in patients with cancer

Abstract: BACKGROUND.The authors compared the relative efficacy and safety of low‐ molecular‐weight heparin (LMWH) and unfractionated heparin (UFH) for the initial treatment of venous thromboembolism (VTE) between patients with and without cancer.METHODS.By using Cochrane methodology for systematic reviews, separate meta‐analyses were conducted for subgroups of patients with and without cancer, and relative risks (RRs) were compared for statistical significance. The methodologic quality for each outcome was assessed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 61 publications
(46 citation statements)
references
References 42 publications
2
43
0
1
Order By: Relevance
“…The first evidence for the association between vascular thrombosis and cancer was presented in 1865 when the French physician Armand Trousseau reported a high incidence of venous thrombosis in patients with gastric carcinomas. Recent clinical and experimental data confirm the relationship between cancer and thrombosis as epidemiological studies showed that 2 out of 10 cancer patients may develop thrombotic complications during the clinical course of their disease (Akl et al ., 2008a,b).…”
Section: Introductionmentioning
confidence: 89%
“…The first evidence for the association between vascular thrombosis and cancer was presented in 1865 when the French physician Armand Trousseau reported a high incidence of venous thrombosis in patients with gastric carcinomas. Recent clinical and experimental data confirm the relationship between cancer and thrombosis as epidemiological studies showed that 2 out of 10 cancer patients may develop thrombotic complications during the clinical course of their disease (Akl et al ., 2008a,b).…”
Section: Introductionmentioning
confidence: 89%
“…However, it is exclusively renally cleared so it cannot be given to patients with a creatinine clearance less than 30 ml/min and is not protamine reversible [40]. A [41]. Equivalent mortality was noted in studies comparing UFH and LMWH with fondaparinux [42][43][44].…”
Section: Initial Anticoagulation For Vte In the Cancer Patientmentioning
confidence: 99%
“…They are used as prophylactic doses in patients with cancer at high risk for VTE. [18][19][20] Thus, the comprehension of the mechanism of action of these LMWHs in cancer-induced hypercoagulability is a prerequisite for the optimization of the antithrombotic treatment. For this purpose, an experimental system for the modelization of hypercoagulability induced by cancer cells and the influence of the latter on the antithrombotic efficiency of LMWHs, fondaparinux, and the direct orally active anticoagulants has been developed and validated.…”
Section: Introductionmentioning
confidence: 99%